Tipologi Kepemimpinan Tgk Ustad di Dayah - Masyrida Masyrida (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was conducted to identify the Islamic Boarding School leadership typology. The research method used is a descriptive qualitative approach. Data obtained through observation, in-depth interviews, and documentation studies were analyzed through the stages of data condensation, data presentation, and verification/conclusion. The research results show that Islamic Boarding School has a strategic role in traditional Islamic education in Aceh, but still faces challenges in developing human resources, especially regarding recruitment, competency and welfare of its teaching staff. Islamic Boarding School has made several efforts to improve the competence of educators, including through the yellow book teaching program for level IX students who are teachers, joint studies between abu and ummi to increase competence, as well as regular religious formation. The proposed recommendations are the need to improve the quality of teaching of the yellow book, develop training and self-development programs for educators, as well as providing awards that motivate educators to improve the quality of education in Islamic Boarding School.